Fine-granulated FEC code for IPTV I-frames over wireless DVB-T channels - Arif, Manar Sami; Habaebi, Mohamed Hadi; Hwegy, Yousef (IIUM Press, 2011)
Powerful Forward Error Correction (FEC) codes are usually used over digital video broadcast (DVB) networks. IPTV uses a base video layer and enhancement layer. In IPTV, the Intra-frame (I-frame) has the highest dependency where corruption of an I-frame will result in error propagation through all the frames in the Group of Pictures (GOP). This phenomena motivates the development of frame-selective fine - granulated FEC schemes in the application layer at the frame level (e.g., GOP) rather than the PHY layer packet level. The objective ofthis letter is to confirm this hypothesis by investigating the GOP peak signal to noise ratio (PSNR) and the bit energy to the noise energy (Et/No) performance for different bit error rate (BER) levels using such fine-granuled Reed-Solomon (RS) FEC coding and Interleaving at the video source before being passed down to the PHY layer. Recent research works have considered the effect of using FEC coding at the application layer for the whole GOP stream in conjunction with the PHY layer [I, 2 among others] but, to the best of the authors' knowledge, none has opted to study the effect of FEC coding to the individual 1frames that forms the base video at the video source before streaming it, in the open literature. Such I-frame protection reduces the required processing time and coding overhead that is most useful when streaming IPTV over satellite links, WiMAX, and other wireless channels.